Myristate and the ecology of AM fungi: significance, opportunities, applications and challenges. Issue 6 (9th April 2020) - Rillig, Matthias C.; Aguilar‐Trigueros, Carlos A.; Anderson, Ian C.; Antonovics, Janis; Ballhausen, Max‐Bernhard; Bergmann, Joana; Bielcik, Milos; Chaudhary, V. Bala; Deveautour, Coline; Grünfeld, Leonie; Hempel, Stefan; Lakovic, Milica; et al.
Summary: A recent study by Sugiura and coworkers reported the non‐symbiotic growth and spore production of an arbuscular mycorrhizal (AM) fungus, Rhizophagus irregularis, when the fungus received an external supply of certain fatty acids, myristates (C:14). This discovery follows the insight that AM fungi receive fatty acids from their hosts when in symbiosis. If this result holds up and can be repeated under nonsterile conditions and with a broader range of fungi, it has numerous consequences for our understanding of AM fungal ecology, from the level of the fungus, at the plant community level, and to functional consequences in ecosystems. In addition, myristate may open up several avenues from a more applied perspective, including improved fungal culture and supplementation of AM fungi or inoculum in the field. We here map these potential opportunities, and additionally offer thoughts on potential risks of this potentially new technology. Lastly, we discuss the specific research challenges that need to be overcome to come to an understanding of the potential role of myristate in AM ecology.